RESILIENCE AS COMMUNAL ECOLOGY: BUILDING SOCIAL CAPITAL OVERCOMING SYSTEMIC BARRIERS FOR TOUR GUIDES IN YOGYAKARTA - Caecilia Dian Eka Pemiastuti; Fx Wahyu Widiantoro (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
This study explores the role of social capital in shaping communal resilience among tour guides in coping with occupational stress and systemic barriers within the tourism sector. A qualitative approach grounded in a social constructivist paradigm was employed. Data were collected through semi-structured in-depth interviews with 10 professional tour guides in Yogyakarta selected through purposive sampling. The data were analyzed using Reflexive Thematic Analysis. The findings reveal that resilience is not solely an individual capacity but is developed through social interaction, collective support, and professional networks. Bonding social capital strengthens emotional support, solidarity, and collective coping mechanisms, whereas bridging social capital facilitates access to information, resources, and advocacy through professional associations. The study proposes a Communal Ecology model, demonstrating that resilience emerges through the interaction of psychological resilience, social networks, and collective learning processes. The findings contribute to tourism resilience literature by highlighting social capital as a critical resource for fostering adaptation and sustainability within tourism communities. ABSTRAK Penelitian ini bertujuan mengeksplorasi peran modal sosial dalam membentuk resiliensi komunal pemandu wisata dalam menghadapi tekanan pekerjaan dan hambatan sistemik di sektor pariwisata. Penelitian menggunakan pendekatan kualitatif dengan paradigma konstruktivis sosial. Data dikumpulkan melalui wawancara mendalam semi-terstruktur terhadap 10 pemandu wisata profesional di Yogyakarta yang dipilih secara purposive. Analisis data dilakukan menggunakan Reflexive Thematic Analysis. Hasil penelitian menunjukkan bahwa resiliensi tidak hanya terbentuk melalui kapasitas individu, tetapi juga berkembang melalui interaksi sosial, dukungan kolektif, dan jaringan profesional. Bonding social capital berperan dalam memperkuat dukungan emosional, solidaritas, dan mekanisme coping bersama, sedangkan bridging social capital memfasilitasi akses terhadap informasi, sumber daya, serta advokasi melalui asosiasi profesi. Temuan penelitian menghasilkan model Ekologi Komunal yang menjelaskan bahwa resiliensi pemandu wisata berkembang melalui interaksi antara resiliensi psikologis, jaringan sosial, dan pembelajaran kolektif. Penelitian ini berkontribusi pada pengembangan kajian resiliensi pariwisata dengan menempatkan modal sosial sebagai sumber daya utama dalam membangun adaptasi dan keberlanjutan komunitas.